Structural Characterization and Cardioprotective Effect of Water-Soluble Polysaccharides Extracted from Clematis flammula - Baaziz, Intissar; Ghazouani, Lakhdar; Rjeibi, Ilhem; Feriani, Anouar; Mnafgui, Kais; Mufti, Afoua; Traikia, Mounir; Le Cerf, Didier; Michaud, Philippe; Pierre, Guillaume; Cherif, Slim (Applied sciences, 2022)
Clematis flammula is widely used for its pharmacological properties in Tunisia. This work aimed to explore, in a rat model, the cardiopreventive capacity of polysaccharides extracted from C. flammula (CFPS) after a myocardial injury caused by isoproterenol. Structural analyses suggested that the average molecular weight of CFPS was 1.82 × 105 g/mol, being mainly composed of glucuronide (41.53%), galacturonic acid (19.06%), arabinose (16.10%), galactose (6.15%), glucose (5.49%), and rhamnose (3.55%). Fourier transform–infrared spectroscopy and nuclear magnetic resonance spectroscopy experiments showed that CFPS was rich with carbohydrates containing pectic materials with glycosidic bonds. In addition, results show that pretreatment with CFPS (150 mg/kg) could improve the electrocardiogram pattern by decreasing the elevated ST segment and ameliorating the relative heart weights and the biochemical profile content (creatine phosphokinase-MB, lactate dehydrogenase, and cardiac troponin I). Furthermore, pretreatment with CFPS reduced the amount of malondialdehyde and restored the genotoxicity induced by isoproterenol. The histopathological study revealed that CFPS pretreatment diminished the level of cardiac tissue injury. Based on these data, CFPS presents a broad biological effect as a cardioprotective and can be used for the exploration of novel natural products for the treatment of cardiac disease.